Comparison of the performance of copper oxide and yttrium oxide nanoparticle based hydroxylethyl cellulose electrolytes for supercapacitors - Chong, Mee Yoke; Arshid, Numan; Chiam, Wen Liew; Ramesh, K.; Ramesh, S. (John Wiley & Sons, Inc., 2017)
Biodegradable solid polymer electrolyte (SPE) systems composed of hydroxylethyl cellulose blended with copper(II) oxide (CuO) and yttrium(III) oxide (Y2O3) nanoparticles as fillers, magnesium trifluoromethane sulfonate salt, and 1-ethyl-3-methylimidazolium trifluoromethane sulfonate ionic liquid were prepared, and the effects of the incorporation of CuO and Y2O3 nanoparticles on the performance of the SPEs for electric double-layer capacitors (EDLCs) were compared. The X-ray diffraction results reveal that the crystallinity of the SPE complex decreased upon inclusion of the Y2O3 nanoparticles compared to CuO nanoparticles; this led to a higher ionic conductivity of the Y2O3-based SPE [(3.08 ± 0.01) × 10−4 S/cm] as compared to CuO [(2.03 ± 0.01) × 10−4 S/cm]. The EDLC performances demonstrated that the cell based on CuO nanoparticles had superior performance in terms of the specific capacitance, energy, and power density compared to the Y2O3-nanoparticle-based cell. However, Y2O3-nanoparticle-based cell displayed a high cyclic retention (91.32%) compared to the CuO-nanoparticle-based cell (80.46%) after 3000 charge–discharge cycles.